2014
DOI: 10.2459/jcm.0b013e328365afb5
|View full text |Cite
|
Sign up to set email alerts
|

Role of hypertension on new onset congestive heart failure in patients receiving trastuzumab therapy for breast cancer

Abstract: New onset CHF occurs seldom in HER2-positive women with EBC, prevalently in the first 6 months of therapy. CHF is associated with a significant reduction in LVEF and is predicted by a history of hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 26 publications
1
11
1
Order By: Relevance
“…15 Arterial hypertension has previously been identified as one of the main factors for ADRC. 16,17 The rate of previous cardiac disease was 6.3%, another finding, which confirms previous investigations. 16 The increasing number of the COT study population might influence the determinants of ADRC because of factors such as age, previous cardiac irradiation, and especially coronary artery disease.…”
Section: Discussionsupporting
confidence: 87%
“…15 Arterial hypertension has previously been identified as one of the main factors for ADRC. 16,17 The rate of previous cardiac disease was 6.3%, another finding, which confirms previous investigations. 16 The increasing number of the COT study population might influence the determinants of ADRC because of factors such as age, previous cardiac irradiation, and especially coronary artery disease.…”
Section: Discussionsupporting
confidence: 87%
“…(61) The decrease in LV ejection fraction by 2D echocardiography in these patients may not be as profound as once thought and usually does not decease to <50%. (61) Similar to the cardiac troponin study, heart failure (overall incidence 3%) was most commonly (in 44% of the cases) observed in the first 3 months of trastuzumab treatment with decreasing frequency thereafter (25%, 19%, and 12% at 3–6, 6–9, and 9–12 months, respectively). Of further note, despite the development of heart failure, trastuzumab was continued in nearly one third of these patients and most intriguingly with partial recovery in LVEF thereafter; no other adverse events were encountered.…”
Section: Cardiotoxicitymentioning
confidence: 90%
“…Of further note, despite the development of heart failure, trastuzumab was continued in nearly one third of these patients and most intriguingly with partial recovery in LVEF thereafter; no other adverse events were encountered. (61)…”
Section: Cardiotoxicitymentioning
confidence: 99%
“…It is possible that a higher proportion of our younger patients received anthracycline-containing therapy, which may worsen cardiac toxicity (76.2% versus 65.5%, p = 0.021). Russo et al [ 21 ] found that patients with hypertension had a relatively higher incidence of trastuzumab-related CHF. They also found that onset of CHF predominantly occurred in the first 6 months of the treatment, which was similar to the findings from our group (median onset of cardiac events 4.54 months; Fig 2A ).…”
Section: Discussionmentioning
confidence: 99%